Carbonic anhydrase 12 mutation modulates membrane stability and volume regulation of aquaporin 5. (1st January 2019) - Hwang, Soyoung; Kang, Jung Yun; Kim, Min Jae; Shin, Dong Min; Hong, Jeong Hee
Abstract: Patients carrying the carbonic anhydrase12 E143K mutation showed the dry mouth phenotype. The mechanism underlying the modulation of aquaporin 5 and function in the salivary glands by carbonic anhydrase12 remains unknown. In this study, we identified the mislocalised aquaporin 5 in the salivary glands carrying the E143K. The intracellular pH of E143K cells was more acidic than that of the cells carrying wild type. To evaluate the role of carbonic anhydrase12 on the volume regulation of aquaporin 5, the submandibular gland cells were subjected to hypotonic stimuli. E143K enhanced the extent of swelling of cells on hypotonicity. Aquaporin 5 modulates water influx through ion transporters to prevent osmotic imbalance. These results suggest that the carbonic anhydrase12 E143K, including acidification or inflammation, mediates volume dysregulation by the loss of aquaporin 5. Thus, carbonic anhydrase12 may determine sensible effects on the cellular osmotic regulation by modulating aquaporin 5.